Survey on understanding of socio-demographic factors responsible for unmet need of family planning from the selected locality in Agra - Shakya, Shilpy; Yadav, Bindhya Chal (International Multidisciplinary Research Journal, 2020)
Despite the progress that has been recorded in area of family planning, an increasing number of women reporting the need for the contraceptives tells the urgency of the situation. Data collected from both developing and developed world put forth a whooping number as 120 million women who have reported that they are willing to delay the pregnancy but are not using any method of contraception. According to world health organization (WHO) Unmet need for family planning is defined as the percentage of women of reproductive age, either married or in a union, who have an unmet need for family planning. The concept of unmet need has already been defined through many studies, as it is the percentage of the women who wish to delay the childbirth but are not using any form of contraception. Since reporting of the unmet need of family planning depends upon the desire of the women to report such an issue which is still considered a taboo in Indian families. It is for this reason; unmet need is called as an inconsistent and fluid indicator of the reproductive potential of the women. It is postulated that, if the unmet need of the selected population is met through interventions, it could help in reducing the population and also help in bringing down child mortality in addition to maternal mortality and morbidity. This study from the selected location from Agra in Uttar Pradesh has brought in light certain observations among the women who were not using any method of contraception. We have through this study have reported that more than 73 percent of the women wanted to stop childbearing. Women who were using any of the choicest method of contraception, among them 34 percent of the women were reporting desire to become pregnant. 67 percent of the women wanted to delay the pregnancy for one to two years, 48 percent of the women from among the selected population in this category did not want to have any more children. The aim of this study was to establish a co-relation between various factors that exerts their affects on presence of unmet need for family planning and use of family planning methods with a reported decrease in pregnancy among the women who did not want any more children.